2004
DOI: 10.1128/aem.70.4.2560-2565.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Production by a Roseobacter Clade-Affiliated Species from the German Wadden Sea and Its Antagonistic Effects on Indigenous Isolates

Abstract: A strain affiliated with the Roseobacter clade and producing a new antibiotic named tropodithietic acid (L. Liang, Ph.D. thesis, University of Göttingen, Göttingen, Germany, 2003) was isolated from the German Wadden Sea. The compound showed strong inhibiting properties with respect to marine bacteria of various taxa and marine algae. Antibiotic production was found to occur during the complete growth phase. Strain mutants without antagonistic properties appeared several times spontaneously.Since the first anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
213
4
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(225 citation statements)
references
References 24 publications
5
213
4
3
Order By: Relevance
“…However, most of them, with the possible exception of the Oceanospirillales species, could not establish stable colonizing populations in the early steps of surface community development, in contrast to the surfacecolonizing Rhodobacterales species. It has been found that certain Roseobacter clade bacteria produce antibacterial compounds when they are growing on a surface, preventing other bacteria, including ␥-Proteobacteria, from colonizing the surface and forming a biofilm (8,10,11,24,44,48). A strain was even found to invade and disperse preestablished biofilms formed by other bacteria (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of them, with the possible exception of the Oceanospirillales species, could not establish stable colonizing populations in the early steps of surface community development, in contrast to the surfacecolonizing Rhodobacterales species. It has been found that certain Roseobacter clade bacteria produce antibacterial compounds when they are growing on a surface, preventing other bacteria, including ␥-Proteobacteria, from colonizing the surface and forming a biofilm (8,10,11,24,44,48). A strain was even found to invade and disperse preestablished biofilms formed by other bacteria (45).…”
Section: Discussionmentioning
confidence: 99%
“…Once the Roseobacter clade bacterial populations reach a certain density, they may actively expel or take advantage of the other surface-attaching bacteria via quorum-sensing-regulated antibiotic production and other mechanisms (8,10,11,24,35,44,45,48,57). Quorum sensing may also be important for multispecies biofilm formation (22,35,58).…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic distribution of these chemolithotrophic gene sets does not map coherently to species phylogeny, suggesting that gain and loss of these traits have occurred multiple times during Roseobacter evolution, consistent with the scenario that roseobacters have continuously explored new ecological habitats. A few of these ecologically relevant genetic traits, including complete photosynthetic gene clusters (58), capabilities for production of the antibiotic tropodithietic acid (TDA) (59,60), and type IV secretion systems (61), are found on plasmids, suggesting that extrachromosomal DNA could be an important mechanism by which genes useful for environmental adaptation are transferred among roseobacters.…”
Section: Genome Contentmentioning
confidence: 99%
“…In order to elucidate the pathways leading to TDA synthesis in strain DSM 17395, we conducted transposon insertion mutagenesis and screened for mutants with reduced pigmentation, which was shown to correlate with TDA production (Brinkhoff et al, 2004;Geng et al, 2008;Berger et al, 2011). Within the framework of this study, we identified 26 genes involved in TDA biosynthesis and pigment production, of which 18 are essential ( Table 2).…”
Section: Tda Biosynthesis In P Gallaeciensis Dsm 17395mentioning
confidence: 99%